Unveiling the effect of three‐dimensional bioactive fibre mesh scaffolds functionalized with silanol groups on bacteria growth. Issue 9 (3rd May 2016) - Rodrigues, Ana I.; Franco, Albina R.; Rodrigues, Fernando J.; Leonor, Isabel B.; Reis, Rui L.
Abstract: The need to replace or repair deteriorating bones and simultaneously prevent the formation of bacteria biofilm without impairing local tissue integration has pushed scientists to look for new designs and processing methods to develop innovative biomaterials. Silicon‐based biomaterials, widely studied for application in bone regeneration, have demonstrated antibacterial properties. Herein, the aim of this work is to investigate the potential of the functionalization of biomaterials surfaces with silanol groups to prevent the bacterial biofilm formation. For that, we evaluated the adherence and biofilm formation of Escherichia coli ( E. coli, Gram negative) and Staphylococcus aureus ( S. aureus, Gram positive) on starch‐based scaffolds. Three‐dimensional fibre meshes scaffolds were developed by wet‐spinning and functionalized with silanol (Si—OH) groups using a calcium silicate solution as a nonsolvent. The functionalization of the scaffolds was confirmed by X‐ray photoelectron spectroscopy. The developed scaffolds showed no biocide activity against the bacterial tested, although the colony‐forming units (CFU) mL −1 counts were significant lower between 4 and 12 h of incubation for both bacteria. The adherence of E. coli and S. aureus to the scaffolds was also investigated. After a growth period of 12 h, the SPCL scaffolds functionalized with Si—OH groups showed a reduced bacterial adherence of E. coli and S. aureus . The functionalized scaffolds showed a positive effect in preventing the formation of biofilm in the case of S. aureus, however, in the case of E. coli this was not observed, suggesting that silanol groups may only have a positive effect in preventing the proliferation of gram‐positive bacteria. The in vitro biological assessment of the functionalized materials showed that these materials sustained cell proliferation and induced their osteogenic differentiation. The outcome of this work suggests that the presence of Si—OH groups in SPCL scaffolds maintained bactericidal activity against S. aureus . Further research is still needed in order to understand the full antibacterial potential of Si—OH groups. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 2189–2199, 2016.